Embodiment and Persuasion. The communicative power of metaphors - Cuccio, Valentina (Rivista Italiana di Filosofia del Linguaggio, 1970)
Persuasion, the ability to linguistically affect other people attitudes and beliefs, has a crucial role in our life, from everyday choices to political orientations. For this reason, understanding its mechanisms is one of the most burning questions for modern societies. Metaphors have always had a special role in research on persuasion, being considered powerful persuasive devices. However, so far, divergent findings have been obtained. As a consequence, the mechanisms and extent of the persuasiveness of metaphors are still partly unknown. The specific role of metaphors in persuasion will be addressed here using a novel approach developed across philosophy, social psychology and neuroscience and through the combination of findings from all these disciplines. On the basis of data from all these different fields, it will be presented and discussed the hypothesis that persuasion can partly rely on the recruitment of bodily experiences and that metaphors are particularly suited to exploiting them. The processing of bodily metaphors (namely, metaphors such as “to see an idea” or “to grasp a concept”, based on bodily experiences) determines the activation of our sensory and motor systems. It will be hypothesized that bodily-based metaphors increase persuasive effects and that their effectiveness relies exactly on the recruitment of the sensory and motor systems